The relationship of CSR and financial performance: New evidence from Indonesian companies - Fauzi, Hasan; Md. Idris, Kamil (Indonesian Center for Social and Environmental Research and Development, 2009)
The research objectives of the study are to investigate whether there are any positive relationships between CFP and CSR under the slack resource theory and to investigate whether there are any positive relationships between CSR and CFP under good management theory by integrating concept of strategic management into the definition of CSR as sustainable corporate performance including economy, social,and environment. To answer the research questions of this study, questionnaire-based survey research design was used. The questionnaires that include items representing variables in this study (corporate social performance, corporate financial performance, business environment, strategy, organization structure, and control system) were sent to the respondents who are managers of state-owned companies(BUMN) and private-owned companies using post and e-mail services. There is a positive relationship between CFP and CSP under the slack resource theory and under good management theory.